Incidence of parastomal and incisional hernia following emergency surgery for Hinchey III-IV diverticulitis: A systematic review. (June 2022) - Mäkäräinen, Elisa; Rautio, Tero; Rintala, Jukka; Muysoms, Filip; Kauppila, Joonas H.
Purpose: The aim of this systematic review was to evaluate the risk of parastomal (PSH) and incisional hernias (IH) after emergency surgery for Hinchey III–IV diverticulitis, with comparison between the Hartmann procedure and other surgical techniques. Methods: The Cochrane Library, Embase, PubMed (MEDLINE), Web of Science and Scopus databases were systematically searched. The primary endpoint was parastomal hernia incidence. The secondary endpoint was incisional hernia incidence. Results: Five studies (four randomized controlled trials and one retrospective cohort) with a total of 699 patients were eligible for inclusion. The PSH rate was 15%–46% for Hartmann procedure, 0%–85% for primary anastomosis, 4% for resection, and 2% for laparoscopic lavage. The IH rates were 5%–38% for Hartmann procedure, 5%–27% for primary anastomosis, 9%–12% for primary resection, and 3%–11% for laparoscopic lavage. Conclusions: Both the parastomal and incisional hernia incidences are poorly evaluated and reported, and varied greatly between the studies.